The exile returned : a self-portrait of the Tamil Vellahlahs of Jaffna, Sri Lanka - Hoole, S. Ratnajeevan H. (Aruvi Publishers, 1997)
Novel, based on the Vellalas, a caste belonging to the Tamils, in Jaffna, Sri Lanka.